1996
DOI: 10.1136/vr.139.4.83
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of anthelmintic resistant nematodes on sheep farms in England and goat farms in England and Wales

Abstract: A survey in 1992 showed that 44 per cent of the sheep farms tested in the south west and 15 per cent of those in the north east of England had parasitic nematode worm burdens which were resistant to benzimidazole anthelmintics, and that 65 per cent of the non-dairy goat farms tested in England and Wales had resistant worms. Ostertagia circumcincta was the main species in sheep and Haemonchus contortus in goats. The resistance to benzimidazoles was diagnosed by a combination of an egg hatch assay and a larval d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 13 publications
(13 reference statements)
2
31
2
Order By: Relevance
“…T. circumcincta is one of the most prevalent specie parasitising small ruminants in Spain (Compair6 Fernfindez and Tarazona Vilas, 1985), while benzimidazoles are the most frequently used anthelmintics in this country (Coles et al, 1993). The results are in accordance with studies in Scotland in goats and sheep which have shown Teladorsagia species to have the greatest propensity for developing resistance to the benzimidazoles (Jackson et al, 1992a), while in England, T. circumcincta seems to be the main species in sheep and Haemonchus contortus in goats (Hong et al, 1996). The presence in the post-treatment larval cultures of Oesophagostomum and Trichostrongylus suggests either the possibility of resistance in these species or a lower efficacy of netobimin against these species.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…T. circumcincta is one of the most prevalent specie parasitising small ruminants in Spain (Compair6 Fernfindez and Tarazona Vilas, 1985), while benzimidazoles are the most frequently used anthelmintics in this country (Coles et al, 1993). The results are in accordance with studies in Scotland in goats and sheep which have shown Teladorsagia species to have the greatest propensity for developing resistance to the benzimidazoles (Jackson et al, 1992a), while in England, T. circumcincta seems to be the main species in sheep and Haemonchus contortus in goats (Hong et al, 1996). The presence in the post-treatment larval cultures of Oesophagostomum and Trichostrongylus suggests either the possibility of resistance in these species or a lower efficacy of netobimin against these species.…”
Section: Discussionsupporting
confidence: 80%
“…First, goats could have acted as carriers of anthelmintic resistant strains of nematodes since they were originally imported from the UK, where a high prevalence of anthelmintic resistance in fibre producing goats has been recorded (Jackson et al, 1992b;Hong et al, 1996). The other possibility is the acquisition of resistance once the animals arrived in Spain.…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of sheep farms with resistance to the benzimidazoles in Scotland (Mitchell et al 1991) and the east of England (Hong et al 1996) is around 14%. But in more recent studies the percentage of flocks resistant to benzimidazoles in Scotland is around 64% (Bartley et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The main factor evoked to select for resistance concerns treatment frequency and, "a large number of anthelmintic treatments with the same anthelmintic family for years" is taken as the key factor for selecting for resistance [91]. This statement is supported by surveys realised on a regional scale, in New Zealand [59,83]; in Malaysia [33]; in South Africa [95]; in the United Kingdom [53,75]; in Australia [36,72]. The "same" repeated anthelmintic treatment is a major cause, in experimental and oversimplified conditions (three-month-old lambs, synchronous infestation with only one to three gastro-intestinal nematode species...) of positive correlation between intensity of resistance and treatment frequency [5,66,71].…”
Section: Introductionmentioning
confidence: 99%